ANALISIS KESULITAN PADA MATERI STATISTIKA KELAS VIII SISWA SMP - Febrianti, Vivie; Chotimah, Siti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to analyze students' difficulties in solving questions on statistics material. This research method uses qualitative methods with a qualitative approach. Processing data in this study using a percentage formula to see the difficulties experienced by students. Retrieval of data in this study used the results of the student answer test based on statistical question instruments with indicators of student achievement; 1) linking mathematical ideas into diagrams, 2) explaining mathematical ideas, situations, and mathematical relations orally or in writing with graphs and algebra, 3) expressing everyday events into language or mathematical symbols, 4) making mathematical models of situations and solving them, 5 ) compile questions about the statistics that have been studied. Based on the results of the study, the difficulty of students in solving questions on student statistics material was 83% still unable to connect mathematical ideas into diagrams and on the indicator r to explain ideas, situations, and mathematical relationships orally or in writing with graphics and algebra, which were not able to compose questions in accordance with what has been learned, as many as 88% of students still experience difficulties to compile a question including the high category. The contributing factor is that students have not been able to understand the basic concepts of statistics, on average students have difficulty understanding the meaning of the questions and it is difficult to determine how to solve the questions.